Education Exploring The Role of Augmented Reality in Enhancing Student Engagement and Learning Outcomes Across Education Levels - Dewanto, Riski; Pujianto, Pujianto; Wiyatmo, Yusman; Yani, Adam Daffa Ghifari (FKIP Universitas Lampung, 2024)
This study aims to explore the role of Augmented Reality (AR) in enhancing student engagement and learning outcomes across various educational levels, focusing on its effectiveness compared to traditional teaching methods. A systematic literature review (SLR) was conducted, gathering relevant articles from the Scopus database based on pre-determined eligibility criteria. The review followed the PRISMA approach to ensure transparency, rigor, and a comprehensive examination of existing research. Initially, 166 articles were identified, with 32 meeting the inclusion criteria after a thorough screening process that assessed the title, abstract, and full text. Thematic analysis was employed to synthesize the findings, which revealed that AR significantly improves student engagement and understanding of complex concepts, particularly within physics education. Experimental studies demonstrated that students utilizing AR tools consistently outperformed their peers in traditional learning environments, showcasing higher levels of motivation and improved academic performance. Furthermore, the interactive nature of AR fosters a more engaging learning experience, prompting students to participate actively in their educational journey. However, the review also identified several challenges in implementing AR in educational settings. Issues such as limited access to technology, adequate teacher training, and potential cognitive overload were noted as barriers to effective integration. Despite these challenges, the findings underscore the potential of AR as a transformative educational tool capable of enhancing traditional learning methodologies. In conclusion, integrating AR into educational practices is crucial for fostering interactive and immersive learning experiences that can improve student outcomes. Continued research and investment in AR technologies are recommended to maximize their benefits and address the challenges identified, ultimately enhancing the quality of education across various levels and subjects. This study contributes to the growing body of literature on innovative teaching methods and highlights the importance of adapting educational practices to meet the needs of modern learners. Keywords: augmented reality in education, student engagement, learning motivation, interactive learning technologies, systematic literatrue review. DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1635-1647